2011
DOI: 10.3810/psm.2011.09.1916
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Current Exercise and Diet on Late-Life Cognitive Health of Former College Football Players

Abstract: Former football players reported more late-life cognitive difficulties and worse physical and mental health than former noncollision-sport athletes and nonathletes. A novel finding of the present study is that current dietary fat was associated with more cognitive difficulties, but only in the former football players. These results suggest the need for educational interventions to encourage healthy dietary habits to promote the long-term cognitive health of collision-sport athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…72 Authors of epidemiologic and intervention studies 73,74 have suggested that overall physical activity preserves or improves cognitive function during aging; therefore, the failure to control for current activity levels among retired players versus control groups in most research presented a potential bias. However, only a minority of studies 26,35,38,42,48,52 controlled for the modifiable risk factors, such as diet and physical activity, that accounted for physical activity engagement and exercise frequency. Similarly, only a small proportion of investigators 22,23,28,30,[50][51][52] examined factors such as body mass index, weight-to-height ratio, or cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…72 Authors of epidemiologic and intervention studies 73,74 have suggested that overall physical activity preserves or improves cognitive function during aging; therefore, the failure to control for current activity levels among retired players versus control groups in most research presented a potential bias. However, only a minority of studies 26,35,38,42,48,52 controlled for the modifiable risk factors, such as diet and physical activity, that accounted for physical activity engagement and exercise frequency. Similarly, only a small proportion of investigators 22,23,28,30,[50][51][52] examined factors such as body mass index, weight-to-height ratio, or cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a minority of studies 26,35,38,42,48,52 controlled for the modifiable risk factors, such as diet and physical activity, that accounted for physical activity engagement and exercise frequency. Similarly, only a small proportion of investigators 22,23,28,30,[50][51][52] examined factors such as body mass index, weight-to-height ratio, or cardiovascular health. These factors may affect cognitive functioning: a meta-analysis 75 indicated that being categorized in the overweight or obese range in midlife was a risk factor for dementia later in life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the frequency of concussions increase, the deficits in learning and memory, processing speed, and verbal fluency presented an aggravation trend in university-level football and ice hockey players after one single season [15]. More recent evidence suggested that deficits may remain in partial cognitive domains for two to three years after a SRC [16,17], and even continue to cause neuropsychological dysfunction later in life [18,19]. One recent cross-sectional study including 93 former collegiate players was conducted by Montenigro et al, showing that there were close relationships between SRCs and later-life cognitive consequences [20].…”
Section: Introductionmentioning
confidence: 99%